Effect of Ultrasonication Duration on Colloidal Structure and Viscosity of Alumina–Water Nanofluid - Mahbubul, I.M.; Chong, T.H.; Khaleduzzaman, S.S.; Shahrul, I.M.; Saidur, Rahman; Long, B.D.; Amalina, Muhammad Afifi (American Chemical Society, 2014)
Nanofluids are promising fluids for heat-transfer applications. Low stability and high viscosity are two important drawbacks for practical applications of nanofluids. The aggregation and sedimentation of nanoparticles are related to the colloidal structure of nanofluids, which directly affects the stability and viscosity. An ultrasonic homogenizer can break the aggregation of particles. The aim of this work was to study the effect of the duration of ultrasonic treatment on colloidal structure, including the stability and temperature-dependent viscosity of a nanofluid. Specifically, a 0.5 vol % Al2O3–water nanofluid was prepared using an ultrasonic homogenizer for various durations from 0 to 180 min. The microstructure, colloid and particle sizes, precipitation, and zeta (ζ) potential were analyzed to investigate the aggregation and sedimentation of the nanofluid. The viscosities of nanofluids subjected to ultrasonic treatment for different durations were also measured at different temperatures from 15 to 45 °C. Better particle dispersion, lower particle sizes, smaller colloid sizes, less precipitation, and higher ζ potentials were observed with increasing sonication time. The viscosity of Al2O3–water nanofluid was found to increase with the sonication time up to 60 min and then subsequently decreased. In addition, the viscosity decreased with increasing temperature. The research concluded that more stabler and lower-viscosity nanofluids can be obtained by applying ultrasonic treatment for durations of 90 min or longer.